Electric Bias Induced Degradation in Organic-Inorganic Hybrid Perovskite Light-Emitting Diodes. Issue 1 (December 2018) - Xu, Bing; Wang, Weigao; Zhang, Xiaoli; Liu, Haochen; Zhang, Yuniu; Mei, Guanding; Chen, Shuming; Wang, Kai; Wang, Liduo; Sun, Xiao
Abstract For organic-inorganic perovskite to be considered as the most promising materials for light emitting diodes and solar cell applications, the active materials must be proven to be stable under various conditions, such as ambient environment, heat and electrical bias. Understanding the degradation process in organic-inorganic perovskite light emitting diodes (PeLEDs) is important to improve the stability and the performance of the device. We revealed that electrical bias can greatly influence the luminance and external quantum efficiency of PeLEDs. It was found that device performance could be improved under low voltage bias with short operation time, and decreased with continuous operation. The degradation of perovskite film under high electrical bias leads to the decrease of device performance. Variations in the absorption, morphology and element distribution of perovskite films under different electrical bias revealed that organic-inorganic perovskites are unstable at high electrical bias. We bring new insights in the PeLEDs which are crucial for improving the stability.